Transient response analysis for DC-DC boost converter - Libau, Charles Muling (2014)
DC-DC Boost Converter and Hybrid Posicast Controller is developed and simulated using MATLAB Simulink software. DC-DC Boost converter has a very high overshoot and a very high settling time which produce oscillated output response. In order to overcome this weakness, Hybrid Posicast Controller is used in order to regulate the output voltage to a desire value. Hybrid Posicast Controller operated within the feedback loop of the system. Transfer function of DC-DC Boost Converter are derived and Posicast elements of  and Td can be calculated directly from the transfer function. Single gain, K is used in order to eliminate the overshoot and minimize the settling time. Simulation results show that Hybrid Posicast Controller effectively regulate the output voltage to a desire value even though load resistance and duty cycle have been changed with a various values. DC-DC Boost Converter using Posicast Controller has an excellent performance to overcome unregulated 377$ input voltage, eliminate overshoot and minimize the settling time